2020
DOI: 10.1177/0267659120907439
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo models for research in extracorporeal membrane oxygenation: a systematic review of the literature

Abstract: With ongoing progress of components of extracorporeal membrane oxygenation including improvements of oxygenators, pumps, and coating materials, extracorporeal membrane oxygenation became increasingly accepted in the clinical practice. A suitable testing in an adequate setup is essential for the development of new technical aspects. Relevant tests can be conducted in ex vivo models specifically designed to test certain aspects. Different setups have been used in the past for specific research questions. We cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Nevertheless, this occurs only in the case of less susceptible strains to the selected antibiotic and if renal function is not impaired, in particular during the very early phase of therapy. The use of ECMO has been shown to further alter drug PK, especially in ex vivo studies, primarily due to sequestration of antibiotics in the ECMO circuit, increased Vd and decreased drug CL [17], although the extent of such changes remains poorly characterized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, this occurs only in the case of less susceptible strains to the selected antibiotic and if renal function is not impaired, in particular during the very early phase of therapy. The use of ECMO has been shown to further alter drug PK, especially in ex vivo studies, primarily due to sequestration of antibiotics in the ECMO circuit, increased Vd and decreased drug CL [17], although the extent of such changes remains poorly characterized.…”
Section: Discussionmentioning
confidence: 99%
“…As such, 110 patients for a total of 222 TDMs (CEF, n = 41; TZP, n = 85; MEM, n = 96) were included in the final analysis. Characteristics of the study population are shown in Table 2; APACHE II score on admission was 24 [17][18][19][20][21][22][23][24][25][26][27][28][29] and VA ECMO was used in 33 (30%) patients. Respiratory infections were the most frequent; Pseudomonas aeruginosa was identified in 24 (21%) patients.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, tubing was depleted of the BIOLINE coating layer after rigorous cleaning. Previous studies have also used similar doses of heparin for in vitro ECMO testing [ 18 , 38 ]. However, we were able to maintain the physiological range of RBC, hematocrit ( Figure 2 ), and hemodynamic ( Table 1 ) and blood gas parameters ( Table 2 ) among different testing conditions, consistently with our previous studies using brand new circuits [ 16 ].…”
Section: Limitationsmentioning
confidence: 99%
“…6 Conducting clinical trials in intensive care populations, especially with pediatric patients, are often difficult to perform due to recruitment related issues, differences in ECMO techniques and equipment, and the heterogeneity of underlying pathologies. 13 Ex-vivo studies have demonstrated to be a feasible and efficient alternative to answering key questions regarding drug sequestration and adsorption. [13][14][15][16][17] Decrease in drug concentration over time in a closed loop ex-vivo ECMO circuit can be attributed either to sequestration or organ-independent metabolism, whereas in invivo ECMO studies, changes in drug concentrations are confounded by changes in hepatic or renal clearance, drug interactions, underlying disease pathologies, and use of other extracorporeal methods (i.e.…”
Section: Introductionmentioning
confidence: 99%